2020
DOI: 10.18632/aging.202235
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial nitric oxide synthase/cyclic guanosine monophosphate/protein kinase G pathway activates primordial follicles

Abstract: In mammals, the well-organized activation of quiescent primordial follicles is pivotal for female reproductive reserve. In the present study, we examined the mechanisms underlying primordial follicle activation in mice. We found that endothelial nitric oxide synthase (eNOS) and its downstream effectors, cyclic guanosine monophosphate (cGMP) and cGMP-dependent protein kinase G (PKG), were expressed in pre-granulosa cells and promoted primordial follicle activation, oocyte growth and granulosa cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“… 38 Moreover, during primordial follicle development, FBXW7 inhibits primordial follicle activation via the eNOS/cGMP/PKG pathway. 39 These researches demonstrate the vital regulatory role of FBXW7 in cell cycle, particularly in the germ cell cycle, which corroborates our findings. For the first time, our experiments demonstrated the association between normal FBXW7 function with folliculogenesis and ovarian function, and its dysfunction is largely implicated in POI, thus reinforcing our initial hypothesis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“… 38 Moreover, during primordial follicle development, FBXW7 inhibits primordial follicle activation via the eNOS/cGMP/PKG pathway. 39 These researches demonstrate the vital regulatory role of FBXW7 in cell cycle, particularly in the germ cell cycle, which corroborates our findings. For the first time, our experiments demonstrated the association between normal FBXW7 function with folliculogenesis and ovarian function, and its dysfunction is largely implicated in POI, thus reinforcing our initial hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in the nematode Caenorhabditis elegans, the FBXW7 homologue SEL‐10 coordinates meiosis and post‐transcriptional gene expression during gametogenesis through the MPK‐1/MAPK pathway 38 . Moreover, during primordial follicle development, FBXW7 inhibits primordial follicle activation via the eNOS/cGMP/PKG pathway 39 . These researches demonstrate the vital regulatory role of FBXW7 in cell cycle, particularly in the germ cell cycle, which corroborates our findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Though the functional significance of PPP in primary and later follicle stages has not been elucidated, PPP-mediated nucleotide biosynthesis may be required for oocyte growth. A further study revealed that NOS in primordial oocytes and pre-granulosa cells synthesized NO, which activates cGMP-PKG signaling and subsequently downregulates an E3 ubiquitin ligase, F-box and WD repeat domain containing 7, FBXW7, resulting in the stabilization of mTOR in pregranulosa cells [Zhao et al, 2020]. This process activates KITL expression in pre-granulosa cells, triggers the transduction of KITL/KIT/PI3K/AKT/FOXO3a signaling in oocytes, and consequently promotes primordial follicule activation, oocyte growth, and granulosa cell proliferation in neonatal ovaries.…”
Section: Metabolism In Oogenesismentioning
confidence: 99%
“…This again supported that cfRNAs could be used to predict different-sized follicles’ follicular fluid. Previous studies have shown that cyclic guanosine monophosphate (cGMP) and cGMP-dependent protein kinase G (PKG) were expressed in neonatal ovaries of pre-granulosa cells, promoting primordial follicle activation, oocyte growth, and granulosa cell proliferation ( Tian et al, 2018 ; Zhao et al, 2020 ). This study found that the cGMP-PKG signaling pathway was significantly enriched, which indicated that the activation of the cGMP-PKG signaling pathway may be closely related to the development of follicles.…”
Section: Discussionmentioning
confidence: 99%